Advances in Computer Games 13th International Conference, ACG 2011, Tilburg, The Netherlands, November 20-22, 2011, Revised Selected Papers - Herik, H. Jaap.; Plaat, Aske.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 13th Advances in Computer Games Conference, ACG 2011, held in Tilburg, The Netherlands, in November 2011. The 29 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers cover a wide range of topics such as Monte-Carlo tree search and its enhancement, temporal difference learning, optimization, solving and searching, analysis of a game characteristic, new approaches, and serious games.
Keywords: Computer science; Computer Communication Networks; Computer software; Electronic data processing; Computational complexity; Artificial intelligence; Computer Science; Algorithm Analysis and Problem Complexity; Artificial Intelligence (incl. Robotics).; Computation by Abstract Devices; Computer Communication Networks; Discrete Mathematics in Computer Science; Numeric Computing